2003
DOI: 10.1094/phyto.2003.93.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice Growth Stages and Silicon on Sheath Blight Development

Abstract: The objective of this study was to determine the effect of silicon (Si) and rice growth stages on tissue susceptibility to sheath blight (Rhizoctonia solani Kühn) under controlled conditions. Rice plants (cv. Rio Formoso) were grown in pots containing low-Si soil amended with Si at 0, 0.48, 0.96, 1.44, and 1.92 g pot(-1) and inoculated with R. solani at the following days after emergence: 45 (four-leaf stage), 65 (eight-leaf stage), 85 (tillering), 117 (booting), and 130 (panicle exsertion). For plants inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 29 publications
4
35
0
7
Order By: Relevance
“…The increased blast resistance of rice plants when supplied with Si has been attributed to a higher density of long and short silicate cells in the leaf epidermis and/or the existence of a thick silica layer below the cuticle forming a physical barrier that prevents or slows Pyricularia grisea penetration (Kim et al, 2002). Increased concentrations of phenolics, lignins and phytoalexins, enhanced activity of defense-related enzymes (chitinases, β-1,3-glucanases and phenylalanine ammonialyases) and the rapid and strong induction of genes related to host defense against pathogens are the biochemical mechanisms that are potentiated by Si in rice (Rodrigues et al, 2003(Rodrigues et al, , 2004(Rodrigues et al, , 2005Liang et al, 2006;Brunings et al, 2009). This study aimed to determine the effects of Si on the activities of defense enzymes in rice leaf sheaths associated with reduce sheath blight development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased blast resistance of rice plants when supplied with Si has been attributed to a higher density of long and short silicate cells in the leaf epidermis and/or the existence of a thick silica layer below the cuticle forming a physical barrier that prevents or slows Pyricularia grisea penetration (Kim et al, 2002). Increased concentrations of phenolics, lignins and phytoalexins, enhanced activity of defense-related enzymes (chitinases, β-1,3-glucanases and phenylalanine ammonialyases) and the rapid and strong induction of genes related to host defense against pathogens are the biochemical mechanisms that are potentiated by Si in rice (Rodrigues et al, 2003(Rodrigues et al, , 2004(Rodrigues et al, , 2005Liang et al, 2006;Brunings et al, 2009). This study aimed to determine the effects of Si on the activities of defense enzymes in rice leaf sheaths associated with reduce sheath blight development.…”
Section: Introductionmentioning
confidence: 99%
“…POX plays a role in the host defense response through the production of antimicrobial quantities of hydrogen peroxide involved in cell wall lignification and by cross-linking with the cell wall proteins (Chittoor et al, 1999;Torres et al, 2006). The active role of Si in increasing the resistance of rice to blast has been associated with a rapid increase in the concentrations of phenolics and phytoalexins as well as strong and rapid activation of the POX and PR-1 genes (Rodrigues et al, 2003(Rodrigues et al, , 2004(Rodrigues et al, , 2005. Rodrigues et al (2005) reported the strong induction of POX transcripts following infection by P. grisea, which corresponded to an increase in the concentration of lignin.…”
mentioning
confidence: 99%
“…Devido à limitação do emprego de cultivares resistentes, bem como aos aspectos econômicos e ambientais negativos associados ao controle químico, pesquisas têm se voltado para a busca de novas tecnologias. O uso de extratos vegetais (Harish et al, 2008), da aplicação de variadas formas de silício (Seebold et al, 2000;Rodrigues et al, 2003) e de agentes de biocontrole (Vidhyasekaran et al, 1997;Vidhyasekaran et al, 2001) estão entre as possibilidades estudadas.…”
Section: Introductionunclassified
“…Many scientists have confirmed that monocotyledon like grasses deposit opaline silica to regulate biochemical reactions, support the plant and enhance its tolerance to salt, heavy metals and pathogenic fungi (Epstein, 1994;Liang, 1999;Parry and Smithson, 1964;Kaufman et al, 1970;Xing and Zhang, 1998;Inanaga et al, 2002;Datnoff et al, 2005;Datnoff and Rutherford, 2004;Rodrigues et al, 2003). Evidence has shown that silica accumulates mainly in a species' epidermis of the upper part, in the central sclerenchyma tissue of the stele, in the vessel walls, the endodermal walls and the epidermis and subepidermal cells of the proximal end of the thick cord roots (Parry and Kelso, 1975).…”
Section: Introductionmentioning
confidence: 99%